HUBUNGAN ANTARA PENYAKIT GINJAL KRONIK DENGAN STROKE ISKEMIK - , Karmila Novianti ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Background Mortality and morbidity of patients with stroke is still high and still a serious health problem. Chronic kidney disease remains a major public health problem. Incidence and mortality of stroke in patients with chronic kidney disease was higher when compared to the general population. According to Bos et al. (2007) chronic kidney disease is a strong risk factor for the occurrence of haemorrhagic stroke but not ischemic stroke. Objective Knowing the relationship between chronic kidney disease with the incidence of ischemic stroke. Method This study use a cross-sectional design of the medical record data with a sample of medical records of patients hospitalized kidney disease who were divided into groups of chronic kidney disease and non chronic kidney disease who entered on January 1, 2009 through December 31, 2009. The variable studied was chronic kidney disease is it associated with incidence of ischemic stroke, with cuota sampling way. Variable measured and controlled are race and age. While uncontrolled variables are gender, diabetes mellitus, hypertension, history of heart disease, hypertriglyceridemia, hypercholesterolemia and smoking. Result A total of 100 medical records of patients are recorded, which consisted of 45 patients with chronic kidney disease and 55 patients wich were not chronic kidney disease. The frequency of ischemic stroke in chronic kidney disease is 31.3% higher than the frequency of ischemic stroke in patients wich were not chronic kidney disease. The analysis showed that chronic kidney disease have a significant association with ischemic stroke events with a value of RP = 5.76 and 95% CI of 1.74-19.07, p = 0.002 and besides diabetes mellitus are also statistically significant (RP = 4.58, 95% CI = 1.44 to 14.55, and p = 0.01). Conclusion Chronic kidney disease associated with ischemic stroke independently. Diabetes mellitu also associated with ischemic stroke.